Scrutinising Polarisation: Patterns and Consequences of Occupational Transformation in the Swedish Labour Market - Tomas Berglund; Ylva Ulfsdotter Eriksson (Routledge, 2024)
This book scrutinises polarisation in Sweden, identifying patterns and variations in labour market transformation and exploring the consequences in terms of jobs, income, prestige, unionization and employment security, as well as the effects on different social groups. Through a series of empirical studies, it sheds light on changes in the occupational structure and the ways in which these changes interact with other societal trends, such as increased temporary employment, rising migration and decreased unionization, whilst also exploring changes in the evaluation of occupations and attitudes towards trade unions. Drawing on distinctly sociological perspectives, it shows how transformations in society and the labour market have affected conditions for individuals and considers whether these changes reinforce existing inequalities occasioned by polarisation or create new ones. Scrutinising Polarisation considers whether and how the Swedish labour market has polarized – and, if so, what this means for individual employees and labour organizations. It will therefore appeal to scholars with interests in the sociology of work and professions, social inequalities and labour market transformations.
Keywords: 300; polarization; polarisation; labour supply; labour market changes; Sweden; ethnic penalty; the Swedish model; welfare state; occupational prestige; occupational change; occupational structure; sickness; absence; trade unions; industrial relations; digitalisation; digitalization; platform work; occupational health; wages; sociology of work; income inequality